Women as Makers and Guardians of Written Culture in Medieval Galicia. A Preliminary Approach - García-Fernández, Miguel (Madrygal. Revista de Estudios Gallegos, 2023)
Women established a wide range of relationships with written culture within medieval Galician society. However, beyond insisting once again on the difficulties in documenting their literacy and their role as writers or authors, and even as readers –the topics that have been more present in socio-literary studies on medieval women–, the aim of this paper is to offer, based on Galician sources, a preliminary approach to the more complex and, above all, more diverse network that existed between women and written culture, a preliminary approach to the most complex and, above all, most diverse network of relationships that existed between women and written culture, presenting them, above all, as makers and guardians of medieval written culture as promoters, matrons, owners, transmitters or custodians of documentary, literary or epigraphic texts. The aim is, therefore, to offer a global proposal to rethink the relationship of medieval Galician women with written culture in terms of female initiative, promotion or agency and, therefore, to insist on the active participation of women in the production and preservation of the documentary heritage of medieval Galicia.
Keywords: Women; Written Culture; Agency; Galicia; Middle Ages